Report of the Committee of Elections on the returns of the votes for and against referring the action of the convention to the people ([publisher not identified], 1861)
Contains the report and supplementary report from the Committee of Elections regarding the voter returns and having a referendum of the Virginia Convention's actions. These reports indicated that the majority wished for a referendum on whether to secede from the Union, as proposed by the Convention.